Electromagnetic Needle Tracking during Simulated Right Internal Jugular Cannulation. Issue 4 (July 2015) - Faulke, D. J.; Hall, T. H.; Nixon, C.
This study used three-dimensional information from Stealth navigation technology during simulated right internal jugular vein cannulation to define the initial needle trajectory taken when using three approaches: landmark (LM), short-axis (SAX) ultrasound and long-axis (LAX) ultrasound. Nineteen volunteers indicated the entry site and needle direction (track) they would use in performing right internal jugular vein cannulation by the three approaches. The likelihood of cannulation success, arterial puncture and needle direction were recorded. Volunteers were asked to assess the suitability of the simulation system for validity and educational benefit. The SAX track crossed the jugular vein more frequently than the LAX and LM tracks (SAX: 94%; LAX: 80%; LM: 47% [SAX versus LM, P <0.01]). The mean indicated needle direction in the coronal plane for LM, SAX and LAX were -4, 13 and 11 degrees, respectively. The track associated with the LAX technique would have entered the carotid artery by 16% of volunteers. At needle depths of over 40 mm, the track crossed the vertebral artery at the following rates (LM: 11%; SAX: 16%; LAX: 16%). The use of Stealth technology to provide three-dimensional feedback of the needle path taken during simulated right internal jugular cannulation was considered realistic (16/19) and of benefit for 18 of 19 (95%) respondents. The SAX track was associated with the highest likelihood of successful jugular cannulation and the lowest cross rate of the carotid artery. The simulation model using Stealth was considered to be valuable and realistic by participants despite some limitations.